Prognostic value of Gustave Roussy immune score in operable pancreatic adenocarcinoma - (:unkn) unknown (My University, 2023)
Background: The Gustave Roussy immune score (GRIm score) is a laboratory index developed to predict survival in nonsmall cell lung cancer patients undergoing immunotherapy and has shown that the pretreatment value is an independent prognostic factor for survival. In this study, we aimed to determine prognostic significance of GRIm score for pancreatic adenocarcinoma that have not been determined in the literature for pancreatic cancer before. The reason for choosing this scoring is to show that the immune scoring system works as a prognostic marker in pancreatic cancer known as immune-desert tumor via immune properties of microenvironment. Methods: Medical records of patients with histologically confirmed pancreatic ductal adenocarcinoma, who were treated and followed up between December 2007 and July 2019 at our clinic, were reviewed retrospectively. GRIm scores of each patient were calculated at the time of diagnosis. Survival analysis were performed according to risk groups. Results: A total of 138 patients were included in the study. While 111 (80.4%) patients were in the low-risk group; 27 (19.6%) were in high-risk group according to GRIm score. Median OS was 36.9 months (95% Confidence interval (CI): 25.42-48.56) in lower GRIm scores, and it was 11.1 months (95% CI: 6.83-15.44) in higher GRIm scores (P = 0.002). One-two-three-year OS rates were 85% versus 47%, 64% versus 39%, 53% versus 27% for low versus high GRIm scores, respectively. The multivariate analysis revealed that high GRIm score was an independent poor prognostic factor. Conclusion: GRIm can be used as a noninvasive, easily applicable, practical prognostic factor in pancreatic cancer patients.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ONKOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ONCOLOGY; Immunity; pancreatic carcinoma; survival